PENYEMBUHAN LUKA SETELAH PERAWATAN BEDAH PERIODONTAL (Studi Pustaka) - Natalina Natalina; Hari Sunarto (Faculty of Dentistry, Universitas Indonesia, 2015)
Background. Periodontal therapy for treatment of periodontitis involves the elimination of anatomic defect. There are two primary approaches to eliminating these anatomic defects : resective (gingivectomy, osseous resection, and apically positioned flaps), and regenerative surgery (osseous graft, guided tissue regeneration, resorbable barriers, coronally position flaps). Aims. The dentist know the outcomes after periodontal surgery. References. Periodontal regeneration means healing after periodontal surgery that results in the formation of a new attachment apparatus, consisting of cementum, periodontal ligament, and alveolar bone. Periodontal repair implies healing without restoration of the normal attachment apparatus. Histologic evaluation is the only reliable method to determine the true efficacy of periodontal therapies. Discussion. The variables involved in periodontal wound healing to solve how to achieve periodontal regeneration are manipulation of progenitor cell, alteration of pathologically exposed root surfaces, exclusion of gingival epithelium, and wound stabilization. Conclusions. Periodontal surgery usually do not result in periodontal regeneration. Gingival epithelium that proliferates apically can be inhibited by stabilization of the flap margin and regenerative surgery.